2019
DOI: 10.1002/cbic.201900294
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylated Proline Surrogates as Part of “Pro–Pro” Turn‐Inducing Templates

Abstract: Proline is often found as a turn inducer in peptide or protein domains. Exploitation of its restricted conformational freedom led to the development of the d‐Pro‐l‐Pro (corresponding to (R)‐Pro–(S)‐Pro) segment as a “templating” unit, frequently used in the design of β‐hairpin peptidomimetics, in which conformational stability is, however, inherently linked to the cis–trans isomerization of the prolyl amide bonds. In this context, the stereoelectronic properties of the CF3 group can aid in conformational contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Of interest is a study by Lim which demonstrated that the proline residue in proline-rich sequences of peptides binding to SRC homology 3 (SH3) domain and rsp5-domain (WW) could be exchanged for an unnatural N-substituted amino acid, showing that the proline residue is most likely the main recognition feature in PRD binding grooves . Mimicking a Pro-X motif also proved useful toward the development of prolyl oligopeptidase (POP) inhibitors as well as to induce specific secondary structures. …”
Section: Introductionmentioning
confidence: 99%
“…Of interest is a study by Lim which demonstrated that the proline residue in proline-rich sequences of peptides binding to SRC homology 3 (SH3) domain and rsp5-domain (WW) could be exchanged for an unnatural N-substituted amino acid, showing that the proline residue is most likely the main recognition feature in PRD binding grooves . Mimicking a Pro-X motif also proved useful toward the development of prolyl oligopeptidase (POP) inhibitors as well as to induce specific secondary structures. …”
Section: Introductionmentioning
confidence: 99%
“…The model substrate 9 was designed to test this hypothesis (Scheme ) and was constructed from building blocks that were envisioned to template macrocyclization by enforcing proximity of the reactive groups . A meta- formylbenzoic acid derived hydrazone and a gem - di -methylated terminal alkyne were used for the A-block and C-block fragments, respectively, flanking a gabapentin B-block which was envisioned to enforce a GABA-type turn .…”
Section: Resultsmentioning
confidence: 99%
“…The complexity of most SFD contexts require the development of operative research method for direct data extraction [ 28 , 29 ]. Second, should the research be used to support/reinforce the field practices or criticize and question actions and achievements [ 30 ]? Ridde and Dagenais [ 31 ] recommended engaging practitioners in a collaborative research, also identified by some SFD researchers to address contextual challenges [ 25 27 , 32 ].…”
Section: Introductionmentioning
confidence: 99%